Les femmes dans l’industrie musicale canadienne francophone - Bissonnette, Joëlle (Fondation Musicaction, 2022)

Au-delà des "vagues" #moiaussi : Cinq ans de mobilisation féministe en musique au Québec (2017-2022) - Blais-Tremblay, Vanessa; Champagne, Lysandre (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2022)

Jumol-Julia Edéry’s Wedding in Early 20th Century Morocco - Cohen, Judith R. (Canadian Jewish Studies/Études juives canadiennes, 2022)

Alanis Obomsawin: Lifework - Hill, Richard William; Peleg, Hila; Haus der Kulturen der Welt (Prestel Publishing, 2022)
"One of today's most important documentary filmmakers, Alanis Obomsawin has dedicated her life's work to shining a light on the injustices experienced by Canada's Indigenous people. This retrospective monograph features an extensive interview with Obomsawin and includes stills and reflections on her entire career including her most recent series devoted to the rights of Indigenous children. Never shying away from controversy, Obomsawin's films have played a critical role in exposing ongoing systemic bias towards Indigenous populations-from fishing rights and education to health care and treaty violations. Obomsawin is also a graphic artist, and she incorporates her often dream-inspired etchings and prints into many of her films. This volume includes illuminating essays exploring Obomsawin's practice and mission as well as personal commentary from collaborators, archival materials, and photographs from the filmmaker's personal life and professional exploits. As Obomsawin closes in on her ninth decade of life-and fifth decade behind the camera-this beautifully illustrated record of her astounding body of work and tireless efforts on behalf of Indigenous peoples and culture is an inspiring celebration of the power of film to dramatically change the course of history"-- Provided by publisher.

Une médiation de la musique au masculin ? Analyse des dispositifs numériques de médiation de la musique produits par les institutions musicales - Kirchberg, Irina (Digital Studies/Le champ numérique, 2022)
Dans le sillage de l’ouvrage dirigé par Octobre et Patureau (Octobre et Patureau 2018), cet article engage à une réflexion sur le traitement de la question du genre dans les dispositifs numériques de médiation produits par des organismes de diffusion et de production musicale. Les études en sociologie du travail artistique (Coulangeon et Ravet 2003 ; Buscatto 2007 ; Bousquet et al. 2018) ne cessent de montrer que l’ensemble des mondes de la musique, aussi bien classiques que jazz ou pop, est traversé par une double ségrégation genrée horizontale (répartition sexuée selon le type d’emploi) et verticale (moindre accès aux postes à responsabilités). On pourrait imaginer que les producteurs de dispositifs numériques de médiation de la musique, portant des valeurs de vivre-ensemble, d’inclusion sociale et d’agentivité (Perez-Roux et Montandon 2014 ; Carrel 2017), et conscients des effets normatifs et prescriptif des supports éducationnels (Octobre 2014), viennent questionner ces frontières. Le « dénombrement » et l’analyse de « cas » tirés du dépouillement systématique d’une centaine dispositifs numériques consultables en ligne et produits par des organismes de production et de diffusion musicale permettront de montrer que tel n’est pas le cas.

"[N]ou rasanble" : rassemblements hétérolingues et hétérogènes dans les chansons de Muzion - Leclerc, Catherine (Analyses, 2022)
Muzion a été parmi les tout premiers groupes de rap québécois à faire résonner une parole locale distinctive. Il le faisait dans un français mâtiné d’anglais et de créole haïtien, multipliant les registres et faisant des emprunts à encore d’autres langues. Cet article se penche sur les chansons du premier album du groupe, Mentalité moune morne, à partir de son hétérolinguisme et des questions d’appartenance que celui-ci soulève. Il examine la manière dont Muzion entrelace les langues, mais aussi les interpellations, défaisant l’association entre langue et identité. Le groupe s’adresse ainsi à la fois à une communauté immigrante locale (d’abord haïtienne, mais également pluriethnique et racisée) qu’il québécise, et à une communauté québécoise élargie qu’il pluralise. Le rap permet en outre à ses membres de faire entendre leurs voix individuelles distinctes, notamment grâce à des usages différenciés de la palette plurilingue du groupe. Ce faisant, ce sont les notions même d’appartenance et de communauté que Muzion se trouve à refaçonner, à l’encontre de toute forme d’homogénéisation, de figement ou de stéréotype.

Parcours professionnels de musiciennes migrantes : de la théorie à l'expérience. Note de terrain à propos du colloque Femmes musiciennes du monde tenu les 26 et 27 novembre 2021 au Centre des musiciens du monde - Marcoux-Gendron, Caroline; Champagne, Lysandre (La Revue musicale OICRM, 2022)

“Before I made fims, I was singing” - Obomsawin, Alanis; Gagnon, Monika Kin (Alanis Obomsawin: Lifework, 2022)

Les rappeuses québécoises sur le devant de la scène : autorité lyrique de la voix féminine chez Donzelle et MCM - Simard, Mathieu; Kirouac Massicotte, Isabelle (Analyses, 2022)

Stories I Might Regret Telling You: A Memoir - Wainwright, Martha (Hachette Books, 2022)
The singer-songwriter's heartfelt memoir about growing up in a bohemian musical family and her experiences with love, loss, motherhood, divorce, the music industry, and more. Born into music royalty, the daughter of folk legends Kate McGarrigle and Loudon Wainwright III and sister to the highly-acclaimed and genre-defying singer Rufus Wainwright, Martha grew up in a world filled with such incomparable folk legends as Leonard Cohen; Suzzy Roche, Anna McGarrigle, Richard and Linda Thompson, Pete Townshend, Donald Fegan, and Emmylou Harris. It was within this loud, boisterous, carny, musical milieu that Martha came of age, struggling to find her voice until she exploded on the scene with her 2005 debut critically acclaimed album, Martha Wainwright, containing the blistering hit, 'Bloody Mother F*cking Asshole,' which the Sunday Times called one of the best songs of that year. Her successful debut album and the ones that followed such as Come Home to Mama, I Know You're Married But I've Got Feelings Too, and Goodnight City came to define Martha's searing songwriting style and established her as a powerful voice to be reckoned with. In her memoir, Stories I Might Regret Telling You, Martha digs into the deep recesses of herself with the same emotional honesty that has come to define her music. She describes her tumultuous public-facing journey from awkward, earnest, and ultimately rebellious daughter, through her intense competition and ultimate alliance with her brother, Rufus, to the indescribable loss of their mother, Kate, and then, finally, discovering her voice as an artist. With candor and grace, Martha writes of becoming a mother herself and making peace with her past struggles with Kate and her former self, finally understanding and facing the challenge of being a female artist and a mother. Ultimately, Stories I Might Regret Telling You offers readers a thoughtful and deeply personal look into the extraordinary life of one of the most talented singer-songwriters in music today.